Assessment of the Expression of GLUT1 in Renal Cell Carcinoma and its Various Subtypes - Abdolahi, Mitra; Alam, Mostafa; Ghaffarpasand, Arash; Nouri, Farzad; Badkoobeh, Ashkan; Golkar, Mohsen; Abassi, Kamyar; Torbati, Peyman (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Renal cell carcinoma is one of the most common tumors of the kidney. Glucose transporters, transport glucose, and increased expression of these transporters have been reported in various tumor types. Glucose transporter 1 (GLUT1), the best-known glucose transporter, has an important role at several stages in cancer progression. The overexpression of GLUT1 in the tumor cells indicates an increased proliferation and invasive behavior of the tumor. AIM: This study aims to investigate the expression of GLUT1 in renal cell carcinoma and its subtypes. METHODS: This study is a descriptive cross-sectional study that was performed on patients with renal cell carcinoma. Seventy reports of formalin fixed; paraffin-embedded blocks of renal cell carcinoma were selected from pathology archives. The samples included: clear cell type renal cell carcinoma, RCC clear cell type with sarcomatoid feature, papillary renal cell carcinoma, and chromophobe renal cell carcinoma. RESULTS: In this study, 50 male and 20 female samples (71.4% and 28.6%) with the mean age of 57.9 ± 13.1 years were studied. Forty-three samples (61.4%) were positive for GLUT1 and 27 (38.9%) were negative for it. For the GLUT1 expression being positive or negative between the two groups, was not significantly affected by the age, sex, and the grade of the tumor, </AQ17>while the difference between the two groups was statistically significant in terms of stage and type of tumor (p < 0/001, p = 0.039). CONCLUSION: Renal cell carcinoma of ccRCC type is associated with increased GLUT1 expression. Therefore, the GLUT1 immunohistochemistry marker can be a useful marker for diagnosis of RCC, specifically ccRCC type.